Spiritual Entrepreneur - Abdul Wadud Nafis (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2011)
Entrepreneur that combines professionalism and spirituality will generate worldly profit and hereafter. The definition of spirituality intelligence is a person who has more ties to the spiritual and psychological aspect rather than the physical or material aspect. While entrepreneur is a talented person in a making new product, determining the new ways of production, collating the operation of new product presence, marketing and managing capital. In achieving business success, the physical and spiritual factor is required. Spiritual factors cover of skill, piety, honesty, trust, good will and others.